Direct Conservative Esthetic Restoration - A Case Report - Manu Rathee; Mohaneesh Bhoria; Madhuri Dua (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Rehabilitation of lost dental aesthetic is one of the most important concerns for contemporary dentistry. Conservative treatment modality along with aesthetic approaches, such as direct and indirect laminate veneer restorations were the treatment of choice. Laminate veneers are restorations to correct aesthetic deficiencies and discolorations. Direct laminate veneers involve the application of a composite material directly to the prepared tooth surface. This case report discusses the composite mirroring using direct composite laminate veneer technique application to the re-established the aesthetic problems related to discolorations in anterior region.